Computer-aided 3D routing of Instrumentation Cables - Sharma, Neha; Tivari, Rajeev; Palit, Dipesh; Dutta, Praveen (International Journal of Scientific Research and Management (IJSRM), 2021)
This paper presents the process of 3D routing of Instrumentation cables for a thermal power plant using the integration capabilities of Instrumentation, Electrical and 3D modules of SmartPlant[1]. Efficient use of integration linkages amongst various modules of SmartPlant is explained. Workflow of preparing cable schedule for Instrumentation cables in an integrated environment is discussed. The processes of routing the Instrumentation cables in an existing 2D CAD software and in 3D software are compared and rules and constraints applied on cable tray network in 3D module for routing the Instrumentation cables are presented. The output of 3D software based routing of Instrumentation cables is compared with the output of 2D software based routing of Instrumentation cables and presented. Finally, the issues faced during the complete process and their resolutions with learning are discussed.